2018
DOI: 10.1186/s12974-018-1284-4
|View full text |Cite
|
Sign up to set email alerts
|

The role of neutrophil granule proteins in neuroinflammation and Alzheimer’s disease

Abstract: Neutrophils are the innate immune system’s first line of defense. Neutrophils play a critical role in protecting the host against infectious pathogens, resolving sterile injuries, and mediating inflammatory responses. The granules of neutrophils and their constituent proteins are central to these functions. Although neutrophils may exert a protective role upon acute inflammatory conditions or insults, continued activity of neutrophils in chronic inflammatory diseases can contribute to tissue damage. Neutrophil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 118 publications
(190 reference statements)
1
63
0
2
Order By: Relevance
“…The marker with the highest factor loading on the latent variable was NGAL, also known as lipocalin-2. NGAL is a pro-inflammatory molecule selectively secreted in neutrophil granules [4]. It is secreted into peripheral circulation by neutrophils and endothelial cells, and it prevents the growth of bacterial colonies [19,33].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The marker with the highest factor loading on the latent variable was NGAL, also known as lipocalin-2. NGAL is a pro-inflammatory molecule selectively secreted in neutrophil granules [4]. It is secreted into peripheral circulation by neutrophils and endothelial cells, and it prevents the growth of bacterial colonies [19,33].…”
Section: Discussionmentioning
confidence: 99%
“…MPO, an enzyme found mainly in the azurophilic granules of neutrophils, produces reactive oxygen species upon neutrophil degranulation [4,18]. It has been found in increased concentrations in the plasma of patients with AD [37] and elevated levels of both MPO, and oxidative products have been reported in the cortex and hippocampus in AD brains ( [38]).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 20 22 Interestingly, we previously identified RAGE as a direct binding partner and potential receptor for CAP37 and showed that NE and CG could also interact with this receptor. 15 , 23 Here, we investigated whether CAP37, NE, and CG could interact with TLR4. To perform these in vitro binding experiments, we used a complex between TLR4 and the extracellular protein MD-2, which forms the functional pattern recognition receptor.…”
Section: Resultsmentioning
confidence: 99%